LC–MS analysis of urolithin-related metabolites in human plasma reveals glucuronide conjugates as the primary species after 4-weeks of pecan consumption - Min Jeong Kang; Joon Hyuk Suh; Liana L. Guarneiri; Jamie A. Cooper; Chad M. Paton (Journal of Food Bioactives, 2023)
The purpose was to determine whether chronic pecan consumption leads to increases in Urolithin (Uro) levels in humans. Second, was to determine the pattern of Uro changes from 0- to 4-weeks among the Uro isoforms (Uro-A, -B, and -C) and their glucuronide conjugates. Forty Subjects were divided into control (no nut) and pecan (68 grams/day (g/day)) groups. Samples were collected at baseline (0-weeks) and 4-weeks after consuming either no nuts in the diet (control) or 68g/day of pecans in the pecan group. Using liquid chromatography-mass spectrometry (LC-MS), plasma Uro-A, -B, and -C levels and their phase II glucuronide metabolites were measured against known standards at 0- and 4-weeks. Uro-A (0.0-0.1 ng/mL) and -C (0.01-0.5) both increased significantly at 4-weeks while Uro-B was undetectable in plasma. The glucuronide conjugates were significantly higher than their free-forms, and all three conjugates increased from 0- to 4-weeks with Uro-A-glucuronide the highest at 2.6-106 ng/mL.